Advances in condition monitoring of machinery in non-stationary operations : proceedings of the fourth International Conference on Condition Monitoring of Machinery in Non-Stationary Operations, CMMNO'2014, Lyon, France December 15-17 /: proceedings of the fourth International Conference on Condition Monitoring of Machinery in Non-Stationary Operations, CMMNO'2014, Lyon, France December 15-17. ([2016]) - Unknown
No abstract available